Uji Sitotoksisitas Ekstrak Metanol Alga Cokelat (Phaeophyta) Pada Lini Sel Kanker Payudara MCF - 7 - Isma Kurniatanty (UIN Sunan Kalijaga Yogyakarta, 2020)
Marine algae (brown algae) have been considered as a source of bioactive compounds as they may be used as food, material for industry and herbal medicine. The objective of this study was to determine the cytotoxic activity of methanolic extracts of brown algae on breast cancer cell lines (MCF-7 cells) as anticancer candidates. Preperation of methanolic extract of brown algae have been done by using maseration method. The dry brown algae was extracted by using methanol, filtered, then dried. Cytotoxic activity test was conducted by using MTT assay on MCF-7 cells. The result showed that methanolic extract of Turbinaria ornata, T. deccurrens and Sargassum myriocystum had cytotoxic activity on MCF-7 cells with IC50 value of 221,88, 268,34 and 250,23 μg/ ml.